2020
DOI: 10.3389/fnint.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Social Attention and Emotional Face Processing in Autism Spectrum Disorder: Insights From Face Scanning and Pupillometry

Abstract: Frontiers in Integrative Neuroscience | www.frontiersin.org February 2020 | Volume 13 | Article 76 Reisinger et al. Social Attention in ASDfor identifying social attention and emotion recognition deficits in ASD. Detecting differences in emotion recognition explicitly through facial scanning was not as clear. Specific mechanisms within the eye-tracking paradigm may be viable options for assessing treatment-specific outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 60 publications
(97 reference statements)
3
28
1
Order By: Relevance
“…Our results demonstrate decreased social orienting towards faces in ASD compared to TD, which is commensurate with previous studies [ 2 9 , 34 , 52 ]. Similar to Harrop et al’s results [ 27 ], our preschool boys with ASD showed reduced attention to faces compared to TD children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrate decreased social orienting towards faces in ASD compared to TD, which is commensurate with previous studies [ 2 9 , 34 , 52 ]. Similar to Harrop et al’s results [ 27 ], our preschool boys with ASD showed reduced attention to faces compared to TD children.…”
Section: Discussionsupporting
confidence: 93%
“…Based on this observation, studies have focused on the possible link between atypical visual exploration and social difficulties in autism using eye-tracking technology. The majority of these studies have shown decreased attention to social stimuli in individuals with ASD (often referred to as a lack of social orienting) and less time spent on the eye region compared to people with typical development [2][3][4][5][6][7][8][9] which were more evident when using dynamic (as opposed to static) stimuli [10] and naturalistic social interactions [2]. In addition, studies of high-risk children indicate that atypical social orienting emerges early in development, [8,[11][12][13] and shapes future developmental trajectories of children with ASD [5,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Sepeta et al (2012) hypothesise that their results, increased pupillary responses in response to happy faces in the TD group and not in the ASD group, can be explained by an impairment in social reward processing in ASD, since attractive faces with direct eye-contact are known to provoke activation of the ventral striatum, which is part of the neural reward processing system. Reisinger et al (2020) found the opposite effect, increased pupil reactivity in the ASD group compared to TD. In another article by Nuske et al (2014b), the children with ASD had reduced pupillary responses to the fearful expressions of unfamiliar people, relative to the typically developing children.…”
Section: Processing Of Emotional Informationmentioning
confidence: 87%
“…ASD and TD both had a greater pupil dilation to direct versus averted gaze. Sepeta et al (2012) also argue against this hypothesis, since their study shows similar pupillary responses in TD and ASD when watching a fearful or anger face with a direct gaze, as do Reisinger et al (2020). Galazka et al (2019) found that the ASD group looked less at the eyes in their study, but despite this, showed similar pupillary contagion as the TD group.…”
Section: Processing Of Emotional Informationmentioning
confidence: 90%
“…Fixation duration has been used to gain insights into cognitive control capacity; for example, what we remember, 123, 124 how we perform mental computations, 125 read, 126 solve problems, 89, 127–133 compare specific stimuli and make decisions based on integrated pieces of information 134 . Eye‐tracking technology also provides knowledge about regions of interest, and therefore answers essential questions of when and how information is being captured and processed during vision‐oriented tests 92, 135–140 . Of great interest is the time spent on an image; this gaze metric has been widely covered in the scientific literature and is associated with the visual expression of preference 141–144 …”
Section: (Eye‐)tracking the Cognitionmentioning
confidence: 99%